Pengelolaan kegiatan pelatihan berbasis inklusi sosial di Perpustakaan Umum Daerah Kota Tanggerang Selatan - Handyana, Sheila Cahyani; Komariah, Neneng; Kurniasih, Nuning (ARKA INSTITUTE, 2022)
The South Tangerang City Regional Public Library has a social inclusion-based training service for the people of South Tangerang City. This social inclusion-based training activity is carried out to assist the community in improving their skills and aims to improve the welfare of the community. The purpose of this study was to determine the management of training as a social inclusion-based library service at the South Tangerang City Regional Public Library. The research method used a qualitative method with a case study approach and data collection techniques including interviews, observation, and documentation. The results showed that the management of social inclusion-based training organized by the South Tangerang City Regional Public Library is by conducting training planning, implementation, and evaluation.